Teaching Note—Social Work at the Crossroads: Using a Simulation to Increase Interest in Social Work History. - Luquet, Wade; Rivard, Rebecca; Tomczak, Stephen Monroe; Osezua, Victory (Journal of Social Work Education)
Engaging social work students in the early history of the profession has been difficult for most Bachelor of Social Work (BSW) and Master of Social Work programs. Students interested in learning skills to help others often express frustration at the need to learn about the formation of the social work profession. However, like any profession, students and practitioners need to know the roots of their chosen field. This article describes a multiclass simulation based on the Reacting to the Past method of teaching historical events through role play and debate. A survey of student responses collected during a class evaluation indicates that the simulation increased student interest in social work history among BSW and public health students in the class. Access to an instructor's manual and related material is included in the article.